The Influence of Mentoring and Education on the Knowledge of Posyandu Cadres, Especially for the Suku Anak Dalam in Bungo Regency, Jambi Province - Listiawaty, Renny; Kalsum, Ummi; Noerjodianto, Dwi; Haryadi, Haryadi; Adriani, Adriani; Sibuarian, Jodion; Rahayu, Sri; Ridwan, M.; Halim, Rd.; Utomo, Praditia Eko Prasetyo; Sitanggang, Hendra Dhermawan; Nasution, Helmi Suryani; Hasanuddin, Hasanuddin (Jurnal Kesmas Jambi, 2025)
The health status of the Suku Anak Dalam (SAD) community remains a serious concern, particularly regarding mortality, morbidity, nutrition, and reproductive health. Nutritional problems among toddlers, adolescents, women of reproductive age, and the wider community continue to contribute to poor health outcomes. In addition, childbirth and reproductive health complications are still major factors causing high infant mortality rates within SAD communities. This study aimed to evaluate the effectiveness of mentoring and educational interventions for SAD Posyandu cadres in improving their knowledge and practical skills. The study used a pre-experimental method with a one-group pretest-posttest design and was conducted at the SAD community hall in Dwi Karya Bakti Village, Pelepat District, Bungo Regency, Jambi. The study population consisted of all SAD Posyandu cadres, totaling 19 participants. Most cadres were unemployed, with 6 men (31.6%) and 13 women (68.4%). Fourteen participants (73.7%) had low educational backgrounds, while 5 participants (26.3%) had higher education levels. The youngest respondent was 12 years old, and the oldest was 31 years old, with an average age of 18.53 years and a standard deviation of 5.037 years. Statistical analysis showed a p-value of 0.002 (<0.05), indicating a significant increase in knowledge after the educational intervention. Therefore, continuous mentoring and training are recommended to strengthen cadre competencies and sustain independent health services. Strengthening community participation through regular Posyandu activities may also help reduce preventable diseases, maternal complications, and infant deaths among SAD families.